Stable colloidal suspensions of nanostructured zirconium oxide synthesized by hydrothermal process - Arantes, Tatiane M.; Mambrini, Giovanni P.; Stroppa, Daniel G.; Leite, Edson R.; Longo, Elson [UNESP]; Ramirez, Antonio J.; Camargo, Emerson R. (Springer, 2010)
Nanocrystalline zirconium oxide was synthesized by hydrothermal treatment of ZrO(NO3)(2) and ZrOCl2 aqueous solutions at different temperatures and time in presence of hydrogen peroxide. Hydrothermal treatment of zirconium salts (0.25 and 0.50 mol L-1) produced nanocrystalline monoclinic ZrO2 powders with narrow size distribution, which were formed by the attachment of the smaller particles with crystallites size of 3.5 nm, estimated by means of the Scherrer's equation and confirmed by transmission electronic microscopy. Typical monoclinic zirconium oxide X-ray powder diffraction patterns and Raman spectra were obtained for all the crystalline powders. It was observed that the crystallization depends strongly on the temperature, resulting in amorphous material when the synthesis was realized at 100 A degrees C, and crystalline with monoclinic phase when synthesized at 110 A degrees C, independently of the salt used. Zirconium oxide colloidal nanoparticles were formed only at hydrothermal treatments longer than 24 h. The stability of the colloids was successfully characterized of zeta potential, showing an initial value of + 59.2 mV in acid media and isoelectric point at pH = 5.2, in good agreement with previous studies.
Keywords: Colloids; Nanoparticles; Monoclinic zirconia; Synthesis